SISTEM DAN PROSES DALAM PILKADA LANGSUNG: Problem Mobilisasi Dukungan - Reny Yulianti; Diny Frihatin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Efforts to realize a free, democratic, direct, fair and transparent, at least, there are three things needs to be done. First, government regulation no. 6/2005 as the implementation of Law no. 32/2004 needs to be followed and criticized continue to avoid off the right rails. Second, the members of parliament and political figures who became actors support mobilization should not be selfish myself and his group. Third, there needs to be an equation perceptions, commitments and steps to make Pilkadasung not just become a legal way of legitimizing the power to be gained, but more important is how they are after elected as a couple Kada / Wakada can be more capable promoting and prospering the community, in particular villagers.